Chromoanasynthetic Genomic Rearrangement Identified in a N-Ethyl-N-Nitrosourea (ENU) Mutagenesis Screen in Caenorhabditis elegans. Issue 2 (1st February 2016) - Itani, Omar A; Flibotte, Stephane; Dumas, Kathleen J; Moerman, Donald G; Hu, Patrick J
Abstract: Chromoanasynthesis is a recently discovered phenomenon in humans with congenital diseases that is characterized by complex genomic rearrangements (CGRs) resulting from aberrant repair of catastrophic chromosomal damage. How these CGRs are induced is not known. Here, we describe the structure and function of dpDp667, a causative CGR that emerged from a Caenorhabditis elegans dauer suppressor screen in which animals were treated with the point mutagen N -ethyl- N -nitrosourea (ENU). dpDp667 comprises nearly 3 Mb of sequence on the right arm of the X chromosome, contains three duplications and one triplication, and is devoid of deletions. Sequences from three out of the four breakpoint junctions in dpDp667 reveal microhomologies that are hallmarks of chromoanasynthetic CGRs. Our findings suggest that environmental insults and physiological processes that cause point mutations may give rise to chromoanasynthetic rearrangements associated with congenital disease. The relatively subtle phenotype of animals harboring dpDp667 suggests that the prevalence of CGRs in the genomes of mutant and/or phenotypically unremarkable animals may be grossly underestimated.